Análise das características organizacionais das empresas de construção civil - Alencar, Angela Rosi Docena de (2015)
The way you organize a company is determinant for the efficiency of its operation. In this sense, this paper presents an analysis of the main organizational characteristics of the civil construction sector companies. Due to the necessity of collecting information from a representative sample of the population was chosen the Survey method as the basis of procedure for this research. The method allowed obtaining primary data in a systematic way. The instrument adopted for data collection was a questionnaire structured in two parts: One being the identification of the profile of the organization and of the interviewed and the second, being the organizational characteristics. Data collection was conducted in the period between November 2013 and July 2014. The questionnaire was applied to a universe of 125 construction companies working in Curitiba and in its region. Data analysis was based on descriptive statistics and later synthesized in Microsoft Excel 2013. With the SPSS Statistical Package for Social Sciences and Spearman analysis was to map and compare the main activities. Through the analysis it was found that the organizational characteristics show certain conservatism in the organizational structure with a management classified as "highly centralized" and "hierarchical". However, at the the operational level we can see a greater integration of activities, cooperation and exchange of information among those envolved. A positive aspect is investment in new technologies and / or equipments. The data point to a high investment degree realized in the last three years, consistent with the growth rate of these companies in the same period.